Determination of amino acids from the leaves of evergreen oak (Quercus ilex L.) at four different stages of decomposition (Biology and fertility of soils, 1987)
It was established by weak ion exchange resin chromatography that 17 amino acids in proteins and 15 free amino acids account for almost all of the amino acids present in the leaves of evergreen oak (Quercus ilex L.) in four different stages of decompo- sition. No significant change in the amounts of these amino acids was observed in the course of decomposi- tion. The amino acid content of evergreen oak leaves is comparable to that in pine needles and beech leaves.